Periodontal disease in dogs: a series of 43 cases treated in Serra Gaúcha (Research, Society and Development, 2022)
Periodontal disease (PD) is an occurrence of high importance in canine health, and there are reports of patients displaying some degree of it by the age of five. This study aims to evaluate different degrees of periodontal disease through the analysis of dental records of canine patients treated in the Serra Gaúcha region. According to the results, 56% of the evaluated patients had normal dental occlusion, and 44% had type III occlusion (prognathism), mostly brachycephalic dogs. It was found that 41.8% had mild PD, 39.6% moderate PD and 18.6% severe PD. In the adult group, most had mild PD and among senior patients there was a higher occurrence of severe PD. Early diagnosis and monitoring by a dental specialist veterinary are of utmost importance to establish an appropriate treatment plan, regarding the degree of the disease and the patient conditions. Performing further tests such as intraoral radiography helps setting an accurate diagnosis and prognosis of the disease.